Rethinking Female Genital Cutting through Postcolonial lens - Carvalho, Erika (AUC Knowledge Fountain, 2024)
Due to global instabilities, the resulting international displacement and rising inter- cultural tensions within Western societies have relocated gendered cultural practicesat the center of contemporary debates on multiculturalism, social cohesion and migration. In this context, female genital cutting (FGC) has re-emerged as a symbol of savagery, portrayed as a symbol of “otherness”, a true global violation of women’s rights. While the increasing attention given to these practices is a testament to reinvigorated feminist activism, FGC has also been harnessed for the purposes of reproducing colonial discourses about the “Third World”, which have been integral to the revival of many policies and the creation of the “Fortress Europe”. This thesis aims to contribute to new knowledge by illuminating how cultural change and FGC-affected women’s experiences of trauma are shaped by state policies on asylum, migrant incorporation and cultural diversity. In locating inclusion, co-production and power as core issues in both anti-FGC activism and research in this area, I focused on an extensive literature review examining the different academic perspectives on conceptualizations of FGC, communities affected by it and the so called “strategies” for ending female genital cutting. This research focuses on reviewing the work of different authors as well as their theoretical contributions on FGC in the Global South, emphasizing the differences in between the cultural and structural perspectives, that define and divide the thinking from liberal feminists, black feminists and mainstream anti-FGC activism, postcolonial and socio-anthropological research. This thesis also looked into how these different debates continue to play out in approaches to FGC and other culturalized forms of gender-based violence in the Global North focusing also on illustrating the key gaps in relation to community perspectives on FGC prevention and the emergent positioning of the practice as an issue of migration and integration. By reflecting on the experiences behind migration, displacement and resettlement, this thesis focused on demonstrating the intersecting social, cultural, political and economic conditions which sustain women's continuums of violence before and after migration. The conclusion illustrates how the collision of anti-FGC and anti-immigration discourse creates barriers for women to rebuild their lives after violence and displacement. I highlighted how these discourses materialize to perpetuate further trauma and toconstrain women's spaces for action to challenge FGC and other forms of gender-based violence within their communities.